Hierarchical nanostructures incorporated with different enhancement strategies for improved photoelectrochemical performance - Wang, Zhiwei (Nanyang Technological University, 2020)
Photoelectrochemical (PEC) water splitting makes it possible to harvest solar energy and then convert it to storable hydrogen fuel in a one-step reaction. As the product of hydrogen combustion is water, PEC water splitting offers enormous promise when it comes to reducing carbon emission. Since the investigation into PEC water splitting with TiO2 thin films as the photoelectrode, various semiconductors with different nanostructures have been developed as photoelectrodes for enhanced PEC performance. An ideal PEC photoelectrode is characterized by an efficient visible absorption, quick charge collection ability, fast charge transfer and high photostability. As a single semiconductor cannot fulfill all of the requirements, several targeted strategies were thus proposed to satisfy more requirements. However, the incorporation of several targeted strategies into one nanostructure to achieve synergistic effects still remains a challenge due to uncertainties in the interaction between these strategies.